2019
DOI: 10.1111/bcp.13954
|View full text |Cite
|
Sign up to set email alerts
|

Exposure‐response modeling of tocilizumab in rheumatoid arthritis using continuous composite measures and their individual components

Abstract: Aims: Tocilizumab has a direct effect on inflammatory markers. Therefore, composite measures for disease activity assessment in rheumatoid arthritis (RA) using these inflammatory markers may not be suitable for tocilizumab treatment. We used a modelling approach to describe the tocilizumab exposure-response relationship and to investigate the different dynamics of the individual components of the routinely used continuous composite measures.Methods: Pharmacokinetic (PK), clinical and laboratory data were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…As Table 2 shown, whatever K in,CRP or K out,CRP had greater value than those of DAS28, hinting high turnover rate of CRP. K in,DAS28 0.003 h −1 and K out,DAS28 6*10 −4 h −1 were very closed to reported values of tocilizumab (K in,DAS28 0.0037 h −1 ; K out,DAS28 7.2 × 10 −4 h −1 ) ( Bastida et al, 2019 ). While Levi et al reported K in,DAS28 0.011 h −1 and K out,DAS28 15.8 × 10 −4 h −1 using data from 4 phase III studies of tocilizumab, which was almost 2 fold of our estimated DAS28 parameters ( Levi et al, 2013 ).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…As Table 2 shown, whatever K in,CRP or K out,CRP had greater value than those of DAS28, hinting high turnover rate of CRP. K in,DAS28 0.003 h −1 and K out,DAS28 6*10 −4 h −1 were very closed to reported values of tocilizumab (K in,DAS28 0.0037 h −1 ; K out,DAS28 7.2 × 10 −4 h −1 ) ( Bastida et al, 2019 ). While Levi et al reported K in,DAS28 0.011 h −1 and K out,DAS28 15.8 × 10 −4 h −1 using data from 4 phase III studies of tocilizumab, which was almost 2 fold of our estimated DAS28 parameters ( Levi et al, 2013 ).…”
Section: Discussionsupporting
confidence: 47%
“…Due to the blockade of IL-6 signaling, WBP216 can directly inhibit the hepatic production of C-reactive protein (CRP) directly ( Bastida et al, 2019 ) and the erythrocyte sedimentation rate (ESR). Thus, the levels of inflammatory markers (CRP and ESR) rapidly decrease after the initiation of IL-6 blocker treatment, even prior to any improvement in swollen or tender joint counts.…”
Section: Introductionmentioning
confidence: 99%
“…Remission usually occurs in the first five years after the onset and is less common in patients with systemic onset and polyarticular JIA. Therefore, JRA is usually a disease that progresses into adulthood 12 . Compared to previous decades, functional outcomes have improved, but the estimated rate of arthroplasty is still very high.…”
Section: Discussionmentioning
confidence: 99%
“…These findings must be interpreted with caution given the low number of patients of our cohort. Since several studies have reported a concentration-effect relationship for TCZ in rheumatoid arthritis [ 13 , 15 , 20 , 22 ], further research conducted in larger cohorts are needed to explore such a concentration-effect relationship when TCZ is used for desensitization.…”
Section: Discussionmentioning
confidence: 99%